HealthCom 2008 - 10th International Conference on E-Health Networking, Applications and Services 2008
DOI: 10.1109/health.2008.4600122
|View full text |Cite
|
Sign up to set email alerts
|

A framework for assessing ICT preparedness for e-health implementations

Abstract: Electronic health (e-health) is probably one of the most significant contributions of Information Communication Technology (ICT) in present day's healthcare. ICT efficiently bridges healthcare sector and technology for e-health implementation, which is a costly affair due to involvement of considerable amount of planning and investment. Preparedness, on the other hand can be defined as a state of readiness prior taking any action and applicable for implementing any e-health project. Study of preparedness essen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
3
3
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 20 publications
(25 reference statements)
0
8
0
Order By: Relevance
“…The said model has further been extended by Li et al (2009) to assess the preparedness levels focusing on the EHR perspective of e-health. 19 However, the limitations of these two studies 19,20 are that both of the models are conceptual and need empirical validation with real-world data.…”
Section: Readiness/preparedness Studiesmentioning
confidence: 98%
See 2 more Smart Citations
“…The said model has further been extended by Li et al (2009) to assess the preparedness levels focusing on the EHR perspective of e-health. 19 However, the limitations of these two studies 19,20 are that both of the models are conceptual and need empirical validation with real-world data.…”
Section: Readiness/preparedness Studiesmentioning
confidence: 98%
“…However, there are certain limitations, such as (1) high level of abstractness within the model and (2) existing distinct boundaries among the prerequisites that in reality may not necessarily be distinct in nature. 17 To handle this issue, Chattopadhyay et al (2008) have proposed a conceptual model that uses hierarchical graph theory and fuzzy set-based integrated approach to measure ICT readiness of an organization. 19 The authors identified four constructs laid by Wickremasinghe et al (2005) 18 and applied the integrated approach of connected graph theory and fuzzy set theory to measure the preparedness levels at each construct.…”
Section: Readiness/preparedness Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The E-Health readiness constructs can be quantified using graph theory and the Analytic Hierarchy Process (AHP) [46] [47]. The purpose behind the approach is to assess E-Health readiness status mathematically and precisely.…”
Section: Quantification Of Constructsmentioning
confidence: 99%
“…In this step, the constructs and their indicators are expressed using a graph theory (Chattopadhyay et al 2008). The purpose behind this approach is to quantify the constructs and thus rank overall E-Health readiness level (e.g.…”
Section: Methods Of Quantifying Constructs Using Connected Graph Theorymentioning
confidence: 99%